Economic assessment of lemon-based agroforestry systems established in Madhupur Sal forest area of Bangladesh (Progressive Agriculture, 2020)
The study was carried out to determine the economic assessment of lemon-based agroforestry systems established in the Madhupur Sal forest during the period from May 2017 to September 2018. The study selected five lemon-based agroforestry systems viz. Lemon-Mango-Pineapple-Papaya-Ginger, Lemon-Pineapple-Papaya-Banana-Aroid, Lemon-Pineapple-Papaya-Ginger, Lemon-Mango-Turmeric-Red amaranth and Lemon-Litchi-Papaya-Banana along with three replications having 0.13 ha area for each sample plot. The control plots (without lemon plant) for each of the five lemon-based agroforestry systems were also selected. In order to calculate the economic profitability of respective agroforestry systems as well as sole cropping performance, data related to incurred cost, total yield and income from lemon and crop components were collected through practical observation, key informant interview and focus group discussion. The benefit-cost ratio (BCR) and land equivalent ratio (LER) for each of the selected agroforestry systems were also determined. From the study, it has been found that all of the lemon-based agroforestry systems were profitable than their sole cropping in respect of income, BCR, and LER. The net profit (460032 Tk/ha) indicated that the Lemon-Litchi-Papaya-Banana based agroforestry systems were financially more profitable followed by Lemon-Pineapple-Papaya-Banana-Aroid, Lemon-Mango-Pineapple-Papaya-Ginger, Lemon-Pineapple-Papaya-Ginger, Lemon-Mango-Turmeric-Red amaranth based agroforestry systems. But the BCR and LER (3.515 and 1.73) revealed that Lemon-Pineapple-Papaya-Banana-Aroid based agroforestry system was more productive followed by Lemon-Litchi-Papaya-Banana, Lemon-Mango-Pineapple-Papaya-Ginger, Lemon-Pineapple-Papaya-Ginger, Lemon-Mango-Turmeric-Red amaranth based agroforestry systems. Prior to considering the obtained results from the study, it can be concluded that lemon-based agroforestry systems are more profitable than the cultivation of sole cropping.Progressive Agriculture 31 (1): 45-55, 2020